Studies of Connected Networks via Fractional Metric Dimension - Hassan Zafar; Muhammad Javaid; Ebenezer Bonyah (Journal of Mathematics)
Metric dimension is an effective tool to study different distance-based problems in the field of telecommunication, robotics, computer networking, integer programming, chemistry, and electrical networking. In this paper, we study the latest form of metric dimension called fractional metric dimension of some connected networks such as circular diagonal ladder, double sun flower, and double path networks.